1976
DOI: 10.2466/pr0.1976.38.3.703
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions of Mental Illness among Asian and Caucasian-American Students

Abstract: The attitudes and beliefs of 62 Asian American and 81 Caucasian college students toward mental illness were examined. After controlling for demographic and background variables between students, a number of significant ethnic differences emerged. These results were interpreted in the context of Asian subcultural values and implications for psychotherapeutic practice were drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1

Year Published

1978
1978
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 6 publications
2
32
1
Order By: Relevance
“…Asian Americans often define mental health in terms of the ability to control one's thoughts; for example, S. Sue, Wagner, Ja, Margullis, and Lew (1976) found that Asian Americans were more likely than European Americans to believe that mental health was due to the avoidance of morbid thoughts. These include the values of not losing face for one's self or family, avoiding drawing attention to one's self, and using self-control to solve personal problems.…”
Section: Counseling Contentmentioning
confidence: 99%
“…Asian Americans often define mental health in terms of the ability to control one's thoughts; for example, S. Sue, Wagner, Ja, Margullis, and Lew (1976) found that Asian Americans were more likely than European Americans to believe that mental health was due to the avoidance of morbid thoughts. These include the values of not losing face for one's self or family, avoiding drawing attention to one's self, and using self-control to solve personal problems.…”
Section: Counseling Contentmentioning
confidence: 99%
“…In a recent review of literature, Leong (1986) concluded that when Asian Americans (a term that most often refers to American-born Chinese and Japanese) seek counseling, they tend to (a) have a lower tolerance of ambiguity, (b) prefer a structured situation, (c) prefer problem-solving over insight-oriented psychotherapy, and (d) exhibit a lower level of verbal and emotional expressiveness. There is evidence of considerable overlap between Asians and Asian-Americans in the conception of mental health and attitudes toward counseling (Lum, 1982;Sue, Wagner, Ja, Margullis, & Lew, 1976). We speculated that native-born Chinese students should hold perceptions and attitudes similar to Asian-American students and different from American students.…”
mentioning
confidence: 93%
“…For example, traditional Chinese beliefs often attribute behavior problems to supernatural causes such as predetermined destiny stemming from wrongdoing in past lives~Sue, Wagner, Ja, Margullis, & Lew, 1976!, or to predominantly physical causes~Tseng & Hsu, 1970 To the extent that causal attributions influence favored approaches to Cultural Factors in Help-Seeking • solutions, these beliefs might make child psychotherapy seem unproductive to some traditional Chinese parents.…”
Section: Cultural Values and Mental Health Servicesmentioning
confidence: 99%